ANALISIS KEPATUHAN PENGOBATAN DAN PERAWATAN PADA PASIEN DENGAN HIPERTENSI - Ratih Ellyza Putri; Erwin Erwin; Herlina Herlina (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Keperawatan, 2022)
The prevalence of hypertension continues to increase every year, making hypertension the number one cause of death in the world. Reducing the morbidity rate of hypertension can be done by taking drugs or taking medication to the nearest health service, but there are still few patients who are obedient to treatment and care. The purpose of this study was to determine the analysis of adherence to treatment and care in patients with hypertension. This research is a quantitative research with descriptive method. The sampling technique was accidental sampling with 97 respondents and the measuring instrument used was a questionnaire. The results of this study showed that the majority of respondents were >59 years old (66%), female gender (60.8%), education status Senior High School (57.7%), job status not working (69.1%), suffering from hypertension for more than 5 years (75.3%). The results of the discipline of taking medication in the good category (83.5%), blood pressure control discipline in the moderate category (87.6%), regular control to the doctor in the moderate category (64.9%), hypertension diet discipline in the good category (79.4%), regular and correct exercise in the poor category (61.9%), and the results of adherence to treatment and care in the moderate category (79.4%). Adherence to treatment and care for hypertension sufferers is already good, namely the consumption of antihypertensive drugs and regulation of food portions, while proper and regular exercise in hypertension sufferers should be increased.Keywords: Adherence, hypertension, medication